Phosphorus pools in soils under rotational and continuous grazed pastures. Issue 1 (17th September 2020) - Toor, Gurpal S.; Yang, Yun‐Ya; Morris, Matt; Schwartz, Philip; Darwish, Yasmine; Gaylord, George; Webb, Kristen
Abstract: Phosphorus loss from intensively grazed pastures is an ongoing concern in agricultural watersheds. We investigated P pools in fields managed as continuous (stocking rate of 3.55 animal unit [AU] ha –1 ) and rotational (stocking rate of 2.56 AU ha –1 ) cattle grazing pastures. Soil samples from 0–5 and 0–20 cm were collected >12 yr after establishing pastures. Organic matter was significantly ( p < .05) higher, i.e., 2.2% greater at 0–5 cm and 1% greater at 0–20 cm in the continuous than the rotational pasture. The Mehlich 3‐P (M3‐P) was 33.1 ± 8.88 mg kg –1 at 0–5 cm and 17.2 ± 3.10 mg kg –1 at 0–20 cm in the rotational pature and was 91.6 ± 43.87 mg kg –1 at 0–5 cm and 63.6 ± 45.85 mg kg –1 at 0–20 cm in the continuous pasture. The M3‐P saturation ratio at 0–5 cm was in the "above optimum" category in the continuous pasture (0.13 ± 0.067) and in the "below optimum" category in the rotational pasture (0.04 ± 0.012). Of the total extractable P in soils, NaOH–P was the largest fraction (59–72%), followed by HCl–P (12–19%), NaHCO3 –P (7–19%), and H2 O–P (2–9%). We conclude that significantly ( p < .05) less accumulation of labile P pools (i.e., H2 O and NaHCO3 ) in the rotational than the continuous pasture was due to the low stocking rate, which will likely translate to lower P losses to receiving waters.